Surgical timing prevails as the main factor over morphologic characteristics in the reduction by ligamentotaxis of thoracolumbar burst fractures - Juan Ignacio Cirillo; Ignacio Farias; Cristóbal Del Pino; Marcos Gimbernat; Alejandro Urzúa; Carlos Tapia; ZAMORANO PÉREZ, JUAN JOSÉ (My University, 2023)
Abstract Background thoracolumbar burst fractures are associated with spinal canal occupation. The indirect decompression of the spinal canal and reduction of the fragment can be achieved with the distraction of the middle column and ligamentotaxis. Nevertheless, the factors that influence the effectiveness of this procedure and its temporality are controversial. Methods The aim of this observational, cross-sectional study was to evaluate the effectiveness of indirect reduction by ligamentotaxis in thoracolumbar burst fractures according to the fracture’s radiologic characteristics and the procedure’s temporality. Patients diagnosed with a thoracolumbar burst fracture between 2010 and 2021 were submitted to indirect reduction by distraction and ligamentotaxis. A retrospective analysis of radiologic characteristics and temporality of the procedure was performed with an independent sample t-test or Pearson’s correlation coefficient, as required. Results A total of 58 patients were included in the analysis. Postoperatively, ligamentotaxis significantly improved all radiologic parameters (canal occupation, endplates distance, and vertebra height). Still, none of the radiological characteristics of the fracture (width, height, position, sagittal angle) were associated with the postoperative change in canal occupation. The endplates distance and the temporality of ligamentotaxis significantly predicted the reduction of the fracture. Conclusion Fragment reduction effectiveness is more significant when performed as early as possible and adequate distraction is achieved using the internal fixator system. The radiologic characteristics of the fractured fragment do not determine its reduction capacity.
Keywords: burst fracture; ct; decompression; fixation; spinal cord injury; thoracolumbar; trauma; cross-sectional studies; fracture fixation, internal; fractures, compression; humans; lumbar vertebrae; retrospective studies; spinal fractures; thoracic vertebrae; compression fracture; cross-sectional study; diagnostic imaging; human; lumbar vertebra; osteosynthesis; procedures; retrospective study; spine fracture; thoracic vertebra